Pengaruh Kualitas yang Dirasakan, Pengalaman Merek, Kepercayaan Merek dan Kepuasan Pelanggan terhadap Loyalitas Merek - Silvia Ardian; Ferryal Abadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study explores the influence of perceived quality, brand experience, brand trust and customer satisfaction on brand loyalty in Nike shoe products. Perceived quality is considered an important factor affecting customer satisfaction and brand loyalty. The population in this study are customers who have used Nike shoe products. Then the sample used in this study is people in the Jakarta, Bogor, Depok, Tangerang, Bekasi areas who have faithfully used Nike shoe products. In this study, data was collected from 120 respondents who met these criteria. Age 17-45 years. The data analysis technique used is SEM-PLS to test the research model with a sample size of 120 respondents, the sample selected using purposive sampling method. The analysis results show that perceived quality has a positive influence on customer satisfaction, brand experience has a positive influence on customer satisfaction, brand trust has a positive effect on brand loyalty. this study the majority of respondents were male. Therefore, further research can equalize or make gender comparisons. to increase brand loyalty, Nike products must integrate strategies that improve product quality, improve brand experience, build trust, and ensure customer satisfaction. This will create a positive cycle that supports.